Effects of Formic Acid on the Adsorption of K on Modified Clinoptilolite - Qiujue Wu; Yanmin Zhou; Tian Wang (Adsorption Science & Technology)
Adsorption of Escherichia coli K 88 on natural and acid-modified clinoptilolite was studied under ambient conditions. The materials under study were characterized in terms of surface area and cation-exchange capacity (CEC). Our study results indicate that treatment with formic acid can increase the Brunauer–Emmett–Teller (BET) surface area, CEC and adsorption capacity of clinoptilolite. The maximum adsorption on these non-metallic minerals was 25 mg/ml, beyond which the adsorption decreased as the amount of adsorptive increased. Time-dependent studies showed that the adsorption process reached equilibrium after 2 hours. The adsorption on E. coli K 88 increased with increasing concentration of the adsorption agent as well as with increasing concentration of the bacteria in suspension. The desorption of H + was studied by washing with a sterile physiological saline solution for 2 hours. The adsorption–desorption hysteresis suggests that the desorption rate of acid-modified clinoptilolite was much lower than that of natural clinoptilolite (P < 0.05). Acid modification of clinoptilolite increased the amount of bacterial adsorption due to the attractive interactions between the clinoptilolite and the bacteria. This increase may also involve the BET surface area and the surface characteristics of clinoptilolite.